Mean Neutrophils to Lymphocytes Ratio in Patients with Coronary Artery Ectasia - Muhammad Shahjehan Mirza, Mirza Nauman Rahi, M. Ijaz Bhatti, Rajia Liaqat, Irfan Majeed, Usman Javed Iqbal, Wasim Ashraf (Pakistan Journal of Medical & Health Sciences, 2022)
Background: The Neutrophil to Lymphocyte (N/L) ratio has appeared as a novel marker of inflammation for cardiac as well as vascular diseases. Atherosclerosis and inflammatory markers shows a major role in the etiology as well as pathogenesis of coronary artery ectasia (CAE). Objective: This study objective was to know about the mean neutrophils to lymphocytes ratio (NLR) in patients who are known to have Coronary artery ectasia (CAE). Study Design: This study was a Cross Sectional Study. Methodology: Total 60 patients with diagnosis of CAE presenting in cardiac emergency or cardiac OPD and admitted in CCU were enrolled. Coronary angiogram was performed to look for evidence of coronary artery ectasia. A blood sample of 5ml was taken and sent to hospital laboratory to find NLR ratio as per operational definition. All collected data was entered and evaluated in SPSS v23.0. It was stratified for gender, age, BMI, DM (200mg/dl) and HTN (>160/90mmHg) to address effect modifiers. Post stratified, t-test was used to rule out these effect modifiers by taking p-value ≤0.05 as significant. Results: In this study, 60 patients who had Coronary artery ectasia (CAE) fulfilling selection criteria were included from Department of Cardiology, Gulab Devi Hospital, Lahore. In these patients, 37(61.7%) were males and 23(38.3%) were females. Mean age of the patients were 40.5±14.8 years with 18 and 70 as minimum and maximum ages. Mean NLR of the patients were 2.4±1.2 with 0.72 and 4.98 as minimum and maximum values. Conclusion: Elevated Neutrophil to Lymphocyte ratio (NLR) plays a significant role in the pathogenesis of inflammation in patients with coronary artery ectasia (CAE).